2000
DOI: 10.1080/080370500439425
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of Angiotensin-converting Enzyme and Angiotensinogen Genes Polymorphisms with Left Ventricular Structure in Young Normotensive Men

Abstract: Left ventricular (LV) hypertrophy is a strong predictive factor for cardiovascular morbidity and mortality. LV structure and function are influenced by many variables, including genetic background. The potential role of gene polymorphisms of different components of the renin angiotensin system remains controversial. The aim of this study was to determine the influence of deletion/insertion (D/I) polymorphism of the angiotensin-converting enzyme (ACE) gene and M235-->T polymorphism of the angiotensinogen (AG) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…In humans, some experimental evidence suggested an association between the ACE I/D polymorphism and LVH (40). However, recent careful studies have found that this association was inconsistent when additional populations were investigated (24,36,39).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, some experimental evidence suggested an association between the ACE I/D polymorphism and LVH (40). However, recent careful studies have found that this association was inconsistent when additional populations were investigated (24,36,39).…”
Section: Discussionmentioning
confidence: 99%
“…Not all studies in this review excluded subjects on this basis; however, of those that did 17,18,20,21,25,26,35 two studies of American men 17,35 and one of American women 17 still exceeded the upper ASE reference limit of LVM. Chinese men and women and Indian men were still lower.…”
Section: Impact Of Co-morbiditiesmentioning
confidence: 98%
“…Therefore of the 13 cohorts (12 studies) of normal healthy men that would be classified as including people with mild LVH, five would also contain men with moderate LVH. [13][14][15][16][17] The LVM from eight cohorts matched the upper ASE reference limit ( ± 10 g) 12,[18][19][20][21][22][23][24] (two studies included subjects from the cohorts used to create the reference range, 12,22 and one appears to be the study on which the twodimensional reference ranges were based 23 ), and LVM from seven cohorts was less than the upper ASE reference limit. 12,[25][26][27][28][29][30] Of those that were less than the upper ASE reference limit, three studies from Asia 25,26,30 had upper values on average 38 g less than the ASE reference limits for m-mode or two-dimensional measurements.…”
Section: Menmentioning
confidence: 99%
“…In the heart, the Ang II is a potent factor of cellular growth (47) . Although increase in the left ventricular mass has not been verified in individuals with different genotypes for ACE (48)(49) , the local RAS activation with consequent increase of the Ang II in response to mechanical overload induced by physical exercise, seems to increase the protein synthesis in the cardiac myocyte via AT 1 receptors (50)(51) . Hypertrophy in the left ventricle (LV) is a remarkable characteristic in elite athletes (52) .…”
Section: I/d Polymorphism Of the Angiotensin-converting Enzyme (Ace)mentioning
confidence: 99%